Myopic Maculopathy Stabilization in a Child with Progressive Complicated Myopia and Underlying Connective Tissue Dysplasia via Optical Therapy with HAL Spectacle Lenses Inducing Retinal Peripheral Defocus: Clinical Case - Svetlana E. Kondratova ("Paediatrician" Publishers LLC, 2024)
Background. Myopia is a serious medical and social problem specifically due to the high risk of such complications as cataracts, myopic maculopathy, glaucoma, and retinal detachment. Children with connective tissue dysplasia (CTD) syndrome are most subjected to myopia. Prevention of myopia progression in children remains the only effective way to prevent myopic maculopathy. Significant progress in this field has been achieved via optical technologies developed on the basis of peripheral defocus theory. Clinical case description. Patient, 10 years old, with CTD, mild myopia of both eyes with rapid progression, myopic maculopathy, grade 1. Ophthalmic status: spheroequivalent refraction - right eye (-)1.5 diopters / left eye (-)1.75 diopters; vision acuity with monocular correction - 1.0. Fundoscopy: optic disc is pale pink, with clear borders, arteries and veins are well-proportioned, their courses and calibers are intact; choriocapillary layer attenuation in the macular and paramacular zones, "parquet fundus"; areas of pigment redistribution on peripheral retina; no atrophic foci detected; anterior-posterior axis of the right and left eyes - 26.2 and 26.3 mm, respectively. Optical coherence tomography (OCT) has revealed retinal thinning in the upper and nasal sectors in the right eye during the first assessment. The left eye has demonstrated losses of retinal thickness within the middle parafoveal zone and significant thinning in the upper segment. Optical therapy with HAL spectacle lenses (inducing volumetric myopic peripheral defocus) was assigned to control myopia to slow down the pathological axial growth of the child's eyes and to stabilize refraction. 4 months of wearing glasses with HAL lenses has led to the stabilization of dystrophic changes in retina, signs of improvement in several sectors by were observed on OCT. No negative changes were revealed in all parafoveal segments of the left eye. The child was recommended to continue wearing glasses with HAL lenses with dynamic follow-up every 3 months. Conclusion. CTD in children is associated with high risk of complications in case of myopia progression, moreover, retinal pathology can occur even with mild myopia. Optical therapy with HAL spectacle lenses is effective and safe first treatment of choice in the control of myopia in children with CTD, and opens new opportunities in prevention of progressive myopia disabling complications in children, whose treatment results were not previously sufficient.